Ancoragem ortodôntica através de mini-implantes - Ramos, Adriano Peres Borges [UNESP] (2015)
The use of temporary anchorage devices (DAT's) during orthodontic treatment has become a routine procedure both associated with the treatment plan as to clinical procedures formerly very difficult to be realized. Such DAT's feature high versatility of application, low cost and simplified installation. Among the DAT's the mini-implants are the best known. The objective of this work is to approach on the use of mini-implants as a means of orthodontic anchorage, giving emphasis on vertical integration. Information will be presented about the anatomy of mini-implants, installation sites, installation, primary stability, osseointegration, prerequisites such as density of bones and space, and clinical applications. Anchoring with DAT's can be used to: Retraction of anterior teeth; Mesialization posterior teeth; Intrusion of incisors; Intrusion later; Correction of the occlusal plane; Distalization of molars; Verticalization and desimpacção molars; Posterior cross bite; Tractor included; and midline correction. It is noteworthy that such devices are not osseointegrated and thus has facilitated its removal after use. This feature is an additional option such as orthodontic treatment, in order to simplify the mechanics, and in some cases, viable therapy, decreasing the treatment time. The use of miniimplante stands out mainly because they do not allow movement of the docking unit and eliminate the patient compliance